Inculcating Islamic Religious Values to Students During the COVID-19 Pandemic: Between Challenge and Effort - Ratnawati, Siti Rohmaturrosyidah; Yahya, Fata Asyrofi (IAIN Ponorogo, 2023)
This research aims to discuss the challenges of PAI teachers in teaching and inculcating Islamic religious values to students and what efforts they made to maximize the process of inculcating Islamic values to students during the COVID-19 pandemic in Ponorogo Regency, East Java. A qualitative descriptive approach was used, while the data were collected through interviews and observation. The results showed that: 1) among the challenges faced by PAI teachers in inculcating Islamic religious values in students were the ineffective process of inculcating values to students due to time and distance limitations as a result of the prohibition of holding offline classes, the unpreparedness of many parties such as teachers, students, and parents in facing the change during the COVID-19 pandemic, and technology's inability to replace the teacher's role as values inculcator fully; 2) To maximize the process of inculcating Islamic religion values to students, the PAI teachers have tried to work together with parents and the community to take part in it so that the role and synergy of